Electronic Waste Management among University Students: Knowledge, Attitudes, Practices, and the Role of Policy Perception - Trisfa Augia; Mery Ramadani; Aliffa Oktanofrida Hade (Poltekkes Kemenkes Surabaya, 2026)
The rapid increase in electronic waste (e-waste) poses significant environmental and public health challenges, particularly in developing countries such as Indonesia. This study assessed the relationship between knowledge, attitudes, perceptions of government regulations, and e-waste management practices among public health students at Universitas Andalas. This research employed a cross-sectional quantitative design, and data were collected from 298 undergraduate students in Padang, West Sumatra. selected through stratified systematic random sampling. The research instrument used validated questionnaires that measured independent variables related to e-waste, such as knowledge, attitudes, and perceptions, and the dependent variable (practices). Univariate, bivariate, and multivariate analyses used SPSS software. Results revealed that although the majority of students (63.4%) had good knowledge, more than half demonstrated negative attitudes (52.3%) and poor practices (52.7%) regarding e-waste management. There was a significant association between attitude and practice (p < 0.001), as well as between perception of government regulation and practice (p < 0.001). In contrast, the relationship between knowledge and practice was not statistically significant (p = 0.222). These findings underscore that while knowledge is important, positive attitudes and perceptions toward regulatory frameworks are more crucial in influencing responsible e-waste behaviour. The study concludes that fostering positive attitudes and trust in government regulation is vital for improving e-waste management practices among students. Educational interventions and policy reforms emphasizing knowledge enhancement and attitudinal and perceptual shifts are essential for promoting sustainable e-waste management in Indonesia.